ANALISIS AKAD ISTISHNA PADA TRANSAKSI PENGGUNAAN KREDIT KEPEMILIKAN RUMAH SYARIAH (PERUMAHAN BUMI GALUNG MALOANG) - mardatillah, hasfriani (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
Financing is a product issued by financial institutions, both banking and non-banking, conventional and sharia. Financing based on sharia principles is the provision of money or bills based on an agreement or loan agreement between the bank and another party which requires the party financed to return the money or bills after a certain period of time in return or profit sharing. This article reviews the Analysis of Istishna Contracts in Home Ownership Credit Use Transactions. The focus of this research is 1) How to implement the istishna' agreement on Sharia Home Ownership Credit (KPR). The method used in this research is qualitative. The research instrument is observation, interview guide, and the researcher is the key instrument. The data source for this research is the results of interviews with buyers who practice home ownership credit and find that the contract istishna. From field research, it can be explained that the Sharia KPR product in Bumi Galung Maloang Housing uses the Istishna contract instrument, namely a sale and purchase transaction by ordering, to build a house with certain specifications, the location and size have been determined by the developer, consumers only choose the specifications which one does he order, and delivery of the goods is made at a later date, while payment is made in cash, or installments